2015
DOI: 10.1136/neurintsurg-2015-011765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for acute ischemic stroke with cerebral microbleeds

Abstract: BackgroundThe influence of cerebral microbleeds (CMBs) on post-thrombolytic hemorrhagic transformation (HT) in patients with acute ischemic stroke remains controversial.ObjectiveTo investigate the association of CMBs with HT and clinical outcomes among patients with large-vessel occlusion strokes treated with mechanical thrombectomy.MethodsWe analyzed patients with acute stroke treated with Merci Retriever, Penumbra system or stent-retriever devices. CMBs were identified on pretreatment T2-weighted, gradient-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…175 One study found that, in 206 patients treated with thrombectomy for acute ischemic stroke, baseline microbleeds did not predict parenchymal hematoma formation (rate with microbleeds, 16%; rate without microbleeds, 19%) or modified Rankin Scale score at discharge. 176 Other studies did not report thrombectomy subgroups separately. 167 There are insufficient data to assess associations between the presence of baseline CMBs and sICH or outcome in patients treated with intra-arterial thrombolysis.…”
Section: Safety Of Intravenous Thrombolysis and Acute Ischemic Strokementioning
confidence: 99%
“…175 One study found that, in 206 patients treated with thrombectomy for acute ischemic stroke, baseline microbleeds did not predict parenchymal hematoma formation (rate with microbleeds, 16%; rate without microbleeds, 19%) or modified Rankin Scale score at discharge. 176 Other studies did not report thrombectomy subgroups separately. 167 There are insufficient data to assess associations between the presence of baseline CMBs and sICH or outcome in patients treated with intra-arterial thrombolysis.…”
Section: Safety Of Intravenous Thrombolysis and Acute Ischemic Strokementioning
confidence: 99%
“…Collectively, these studies were composed of 1974 patients (study sample size range: 206–717), 480 (24.3%) of which had CMBs on pretreatment MRI scans. From inspection of each of the studies, patients with preexisting CMBs were older, 15 19 had a more severe degree of leukoaraiosis, 15 , 17 , 19 higher rate of diabetes mellitus, 17 , 19 and higher rate of hypertension (or higher systolic blood pressure), 16 , 18 , 19 whereas other baseline characteristics were not significantly different. The characteristics of CMBs are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 98%
“…On the 3.0T scanner, T2∗ GRE sequences were 5 mm slice thickness with slice spacing 6 mm (repetition time, 690 ms; echo time, 20 ms; field of view 240 mm; 30° flip angle; matrix size 320 × 210). 9 …”
Section: Methodsmentioning
confidence: 99%
“… 7 , 8 It is not clear whether CMBs are associated with hemorrhagic complications and mortality after mechanical thrombectomy. 9 …”
Section: Introductionmentioning
confidence: 99%